The Effects of Buffer Nature on Immobilized Lipase Stability Depend on Enzyme Support Loading - Pedro Abellanas-Perez; Diego Carballares; Javier Rocha-Martin; Roberto Fernandez-Lafuente (Catalysts, 2024)
The lipases from Thermomyces lanuginosus (TLL) and Candida antarctica (B) (CALB) were immobilized on octyl-agarose beads at 1 mg/g (a loading under the capacity of the support) and by overloading the support with the enzymes. These biocatalysts were compared in their stabilities in 10 mM of sodium phosphate, HEPES, and Tris-HCl at pH 7. Lowly loaded CALB was more stable than highly loaded CALB preparation, while with TLL this effect was smaller. Phosphate was very negative for the stability of the CALB biocatalyst and moderately negative using TLL at both loadings. The stability of the enzymes in HEPES and Tris-HCl presented a different response as a function of the enzyme loading (e.g., using lowly loaded CALB, the stabilities were similar in both buffers, but it was clearly smaller in HEPES using the highly loaded biocatalysts). Moreover, the specific activity of the immobilized enzymes versus p -nitrophenol butyrate, triacetin and R - or S -methyl mandelate depended on the buffer, enzyme loading, and interaction between them. In some cases, almost twice the expected activity could be obtained using highly loaded octyl-CALB, depending on the buffer. A co-interaction between the effects on enzyme activity and the specificity of support enzyme loading and buffer nature was detected.